2004
DOI: 10.1007/s00432-004-0587-2
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance, its consequences for the clinical course of the disease, and possibilities of correction in endometrial cancer

Abstract: Thus, insulin resistance/hyperinsulinemia is associated with a more aggressive course of the disease in certain groups of the patients but--in contrast to excessive estrogenic stimulation--does not result in increased genotoxic damage in tumor and normal tissues. The data obtained once more confirm the need for treatment and prevention measures aimed at correcting hormonal-metabolic disturbances in endometrial cancer patients and groups at risk of this disease. Such an approach might include use of antidiabeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 32 publications
1
45
0
2
Order By: Relevance
“…Hyperinsulinemia may increase levels of free estrogen through decreasing concentrations of circulating sex hormone-binding globulin (41,42), and several epidemiologic studies have observed an increased risk of endometrial cancer in relation to high prediagnostic C-peptide indicating hyperinsulinemia (43). It has also been suggested that hyperinsulinemia and insulin resistance are associated with a more aggressive course of endometrial cancer (44). Furthermore, hyperinsulinemia through decreasing levels of insulin-like growth factor-binding protein-3 increases circulating free insulin-like growth factor-I, which, by binding and activating insulin-like growth factor-I receptors in the endometrium, stimulates cell proliferation (45)(46)(47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%
“…Hyperinsulinemia may increase levels of free estrogen through decreasing concentrations of circulating sex hormone-binding globulin (41,42), and several epidemiologic studies have observed an increased risk of endometrial cancer in relation to high prediagnostic C-peptide indicating hyperinsulinemia (43). It has also been suggested that hyperinsulinemia and insulin resistance are associated with a more aggressive course of endometrial cancer (44). Furthermore, hyperinsulinemia through decreasing levels of insulin-like growth factor-binding protein-3 increases circulating free insulin-like growth factor-I, which, by binding and activating insulin-like growth factor-I receptors in the endometrium, stimulates cell proliferation (45)(46)(47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%
“…Berstein et al examined the prevalence of insulin resistance in a cohort of women with endometrial cancer, excluding those with a clinical diagnosis of diabetes. 21 In their study, insulin resistance was calculated using preoperative fasting insulin and glucose levels. 22 They reported that 35% of their cohort was insulin-resistant.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, obesity, excess estrogen, type II diabetes, and hypertension are important risk factors for endometrial carcinoma [77,78], but the effects of PPARγ agonists on endometrial carcinoma are largely unknown. Very recently, we examined the expression of PPARγ mRNA and protein in normal endometria and its disorders [79].…”
Section: ) Peroxisome Proliferator-activated Receptor (Ppar) Ligandmentioning
confidence: 99%